Seed lost to perineum from hydrogel spacer after brachytherapy for prostate cancer - Makoto Nakiri; Kosuke Ueda; Ryuji Hoshino; Naoyuki Ogasawara; Hirofumi Kurose; Kiyoaki Nishihara; Koichiro Muraki; Chikayuki Hattori; Etsuyo Ogo; Tsukasa Igawa (IJU Case Reports, 2023)
Introduction We describe a rare case of brachytherapy for prostate cancer in which a seed was lost from the perineum after a hydrogel injection. Case presentation A 71‐year‐old Japanese man was diagnosed with localized high‐risk prostate cancer. Trimodality therapy with I‐125 brachytherapy was selected, and combined androgen blockade therapy was initiated. Brachytherapy and hydrogel injection were performed 7 months after combined androgen blockade initiation; 6 months later, the patient visited our hospital with complaints of redness and bleeding in the perineum. Serous effusion and loss of a seed on the right side of the perineal anus were observed. Pelvic magnetic resonance imaging showed a tunnel like discharge of hydrogel from the dorsal prostate to the perineum. The fistula was incised, the seed was removed, and drainage was performed. Conclusion Appropriate diagnosis and treatment with careful follow‐up are required in patients at high risk of infection after brachytherapy with hydrogel injection.